Performative actions, rights and mediatization: the case of Jóvenes Republicanos (Argentina) - Camezzana, María Daniela (2023)
This article analyzes two actions carried out in 2021 by Jóvenes Republicanos (JR) - a right-wing Argentine political group - and their media coverage. The hypothesis is that JR adopts performative elements as a means to introduce themselves into the public sphere. Their first performance thematized the pandemic and, particularly, the vaccination process, while the second one, the high poverty rates. Both took over the streets, sparked controversy and allowed us to see the strong link between the right wings and online activism. The methodology used in this study is qualitative, based on the analysis of the discourses delivered by leaders and on the virtual ethnography of different social networks. The performances are also described, analyzed, and compared.